Novel Prognostic Predictor for Primary Pulmonary Hypertension: Focus on Blood Urea Nitrogen - Hu, Bo; Xu, Guangtao; Jin, Xin; Chen, Deqing; Qian, Xiaolan; Li, Wanlu; Xu, Long; Zhu, Jia; Tang, Jie; Jin, Xiuhui; Hou, Jian (Frontiers in Cardiovascular Medicine, 2021)
Background: Primary pulmonary hypertension (PPH) is a life-threatening disease associated with increased mortality. The urea cycle pathway plays a major role in PPH severity and treatment response. Little is known about the association of the blood urea nitrogen (BUN) and PPH prognosis. Methods: Clinical data were extracted from the Medical Information Mart for Intensive Care III (MIMIC-III) database. Adult patients (≥18 years) patients with primary pulmonary hypertension (PPH) in the database were enrolled. Spearman correlation was used to analyze the association of BUN with length of hospital and intensive care unit (ICU) stays. The chi-square test was used to analyze the association of BUN with mortality rate. Survival curves were estimated using the Kaplan-Meier method and compared by the log-rank test. Multivariable logistic regression was used to identify the BUN as an independent prognostic factor of mortality. Receiver operating characteristic (ROC) curves and the area under the curve (AUC) were used to analyze the sensitivity and specificity for mortality. Results: In total, 263 patients who met the selection criteria were enrolled. BUN was significantly positively associated with length of hospital stay and ICU stay (hospital stay: ρ = 0.282, ICU stay: ρ = 0.276; all P < 0.001). Higher hospital, 90-day and 4-year mortality rates were observed in the higher BUN quartile of PPH patients (hospital: P = 0.002; 90-day: P = 0.025; 4-year: P < 0.001). The Kaplan-Meier survival curves showed that patients in higher BUN quartile tended to have lower 4-year survival (Q1:7.65%, Q2: 10.71%; Q3: 14.80%, Q4: 16.84%; P < 0.0001). Logistic regression analyses found a significant association of BUN and mortality (hospital: OR = 1.05, 95% CI = 1.02–1.08, P = 0.001; 90-day: OR = 1.02, 95% CI = 1.00–1.05, P = 0.027; 4-year: OR = 1.05, 95% CI = 1.02–1.08, P = 0.001). Results of ROC and AUC showed that the diagnostic performance of BUN for mortality was moderately good. Conclusion: BUN was positively correlated with the length of hospital stay and ICU stay of PPH patients. Higher BUN was associated with higher hospital, 90-day and 4-year mortality and lower 4-year survival of PPH patients. These findings indicate that BUN can be a novel potential prognostic predictor for PPH.